The mysterious ultra high energy cosmic ray clustering - Anchordoqui, Luis A. (2001)
We examine the correlation between compact radio quasars (redshifts in the range z = 0.3–2.2) and the arrival direction of ultrahigh energy cosmic rays forming clusters. Our Monte Carlo simulation reveals a statistically significant correlation on the AGASA sample: the chance probability of this effect being less than 1%. The implications of this result on the origin of ultrahigh energy cosmic rays are discussed.